Development of Green Bromination Titration for Determination of Ciprofloxacin Hydrochloride in Different Pharmaceutical Dosage Forms (Indonesian Journal of Chemical Science, 2022)
Ciprofloxacin Hydrochloride (CIP-HCl) is a second-generation synthetic fluoroquinolone used for a wide range of infectious diseases. This study set out to provide a handy, cost-effective, facile, and eco-friendly analytical technique titrimetric method (method A). The developed titrimetric method is based on the bromination of CIP-HCl by bromine produced in situ by the reaction of acid on the bromate-bromide mixture. Alongside, simple UV-Spectroscopic (method A) from previous literature was conducted. Titrimetric allows the determination over the range of 5.0-70.0 mg CIP-HCl while in UV-spectroscopic, Beer’s law is obeyed in the concentration ranges of 3.5-11.5 μg mL-1. The result of the proposed method was compared statistically with the reference UV-spectroscopic method from the literature. Student’s t-test and F-ratio at 95% confidence level were used for comparison. The result showed no significant differences between the developed method (method A) and the reference method (method B) in regards to accuracy and precision. The developed method and UV-spectroscopic were applied effectively for the determination of the CIP-HCl in three different dosage forms (tablet, infusion, and eyedrops), with three brands for each dosage form.